A Novel Pentapeptide Targeting Integrin β3-Subunit Inhibits Platelet Aggregation and Its Application in Rat for Thrombosis Prevention - Qu, Qingrong; Liu, Yamin; Yan, Xuejiao; Fan, Xiaobo; Liu, Naifeng; Wu, Guoqiu (Frontiers in Pharmacology, 2016)
Background: Antiplatelet therapy plays a pivotal role in the prevention and treatment of thrombotic diseases. We reported the screening of P1C as a novel integrin-binding peptide from the C-terminal of connective tissue growth factor. Primary study indicated that P1C has potential against platelet aggregation. Objectives: In this study, we aimed to find the shortest active unit from the P1C fragments and explore its in vivo and in vitro activities. Methods: A series of truncated P1C fragments was prepared and screened for antiplatelet activity. The most active fragment was evaluated using coagulation assays. Flow cytometry and confocal microscopy were used to determine the interaction between the peptide and the integrin. The in vivo potential was further explored using two types of rat models. Results: From a series of truncated P1C forms, a so-called P1Cm peptide of 5-amino acids, namely, IRTPK, was screened out as the shortest active unit with superior activity. Coagulation experiments and an in vivo toxicity assay demonstrated that P1Cm is safe in vivo and inhibits ADP- and TH-induced human platelet aggregation in vitro in a concentration-dependent manner. Furthermore, it has limited effect on the coagulation parameters. Flow cytometry and confocal microscopy experiments consistently indicated that the peptide specifically binds the β3-subunit of integrin on platelets. Further experiments using rat models of artery-vein shunt and carotid arterial thrombosis illustrated that P1Cm can effectively prevent thrombosis formation. Conclusion: All the results suggested that P1Cm may be a new, promising antithrombotic alternative to currently available antiplatelet treatments.